Legal Perspective of E-Banking Fraud in India (International Journal of Innovative Research in Engineering & Management, 2022)
The financial industry plays a critical part  in a country's economic growth. An economy's lifeblood is  banking. For economic progress, a robust and healthy  financial sector is essential. Indian the banking sector is  now undergoing an IT revolution. The process of  implementation. The use of the internet in banking has  revolutionized the industry. It has been successful. Both  customers and banks profited from it. In India, e-banking  has grown in popularity. Several changes have occurred as  a result of technological advancements and innovation.  The arrival of the card, Immediate Payment Service, Clear  The notion of internet banking and mobile banking, as well  as the transfer of funds, are the There have been a number  of changes in the banking industry. E-banking is a term  that encompasses a variety of services. Online shopping,  fund transfer, and mobile banking are all included in this  phrase etc. The bank hopes to teach the basic notion of IT  via E-Banking. Included Services that are based on the  Internet. System of conventional banking it is more  convenient for consumers to make debit payments.as well  as credit several of the factors why e-banking is gaining  popularity in India is because People’s use of the internet  is becoming more widespread. Because of the many  benefits, electronic banking is becoming more popular. It  is linked to it. However, it has raised certain concerns and  obstacles. In terms of cybercrime, such as data theft,  phishing, and credit card fraud, this paper attempts to  provide an overview of electronic banking.in India, as well  as the many concerns and challenges that the banking  sector faces.
Keywords: Banking; Consumers; Fraud; Fund; Payment